Evaluation of cellulose selective dissolution systems for recycling cellulosic waste - Chow, JiaHui (Nanyang Technological University, 2022)
While pollution generated from synthetic polymers have been observed to have detrimental effects on our environment. In a bid to reduce the pollution and to ensure a sustainable polymer source, polymer recycling and returning to biological polymers are solutions studied by various research teams. Regenerated cellulose, a soluble cellulosic derivative achieved from the conversion of natural cellulose and regeneration, is becoming a popular strategy to moderate the demand of cellulosic materials using environmentally benign and sustainable solutions. However, due to the complex cellulose network, extended noncovalent interactions amongst molecules and partial crystalline structure, challenges are faced during chemical processing of cellulose. This hinders their application of cellulose as a green biopolymer alternative. This study seeks to ultimately contribute to the understanding and improvement of the dissolution of cellulose in various solvent solutions. Various dissolution solvent systems were evaluated in terms the effectiveness of dissolving cellulose and the ability to separate out cellulose from cellulosic wastes, such as textiles, environmental impact, cost and biodegradability. Each of the systems have their own advantage and disadvantages but result from this study indicated success in NaOH and Urea, [TBPH] and ZnCl2 and urea dissolution systems. The crystalline structure of alpha cellulose mixed with these systems was transformed from type I to type II cellulose after regeneration due the interruption in hydrogen bonding of cellulose. The regenerated cellulosic materials were also characterized by X-ray diffraction techniques (XRD). This project identified the potential of greener dissolution solvent systems for recycling cellulosic wastes but future studies should investigate the effect of reducing molecular weight of cellulose during dissolution for subsequent pretreatment or biodegradability of cellulose.